Political campaign analysis of #BlackLivesMatter and #PapuanLivesMatter hashtag activism on Instagram: Comparative perspective - Allymatul; Nurdin (Universitas Islam Malang, 2026)
This research compares the political campaigns of the Instagram hashtag activism movements #BlackLivesMatter and #PapuanLivesMatter in their efforts to combat racism and discrimination. Using a qualitative netnographic approach grounded in the theory of contentious politics, the study evaluates the effectiveness of both digital campaigns in encouraging political and institutional change in the United States and Indonesia. Data were collected through literature review, documentation, and netnographic analysis of Instagram content from both movements. The findings reveal that #BlackLivesMatter successfully gained broad political support in the United States and encouraged institutional reforms within the police system to support anti-racism and anti-discrimination policies. In contrast, #PapuanLivesMatter has not effectively transformed public social consciousness in Indonesia. This limitation is associated with the political interests of pro-independence Papuan elites seeking separation from Indonesia, which reduced broader political and public support for the movement. Despite these differences, both hashtag activism movements contributed to raising global awareness of racism and discriminatory practices within identity politics across various countries, including the United States and Indonesia. This study contributes to the field of contentious politics by demonstrating that hashtag activism can function as a digital political communication strategy for governments and social movements in addressing social, economic, and cultural issues in the digital era. Furthermore, the research enriches the concept of digital politics by showing that hashtag activism can enhance public political participation, as well as the transparency and accountability of political institutions at both national and local levels.